Pomegranate, its Biological Characteristics and Economic Significance - Marufjanov Abdurakhman Mosinjon ugli (Web of Journals Publishing, 2023)
In the conditions of Uzbekistan, pomegranates are buried before winter. When drawing up technological cards, the main attention is focused on the selection and implementation of economically efficient methods of growing agricultural products in the conditions of the farm. The model technological map of pomegranate cultivation in pomegranate orchards with buried crops on irrigated lands is based on the latest scientific and technological achievements and advanced practices, and includes a total of 29 agro-measures.
Keywords: Pomegranate, technological card, agrotechnical activities.